Naturopathy and yoga in ameliorating multiple hormonal imbalance: a single case report - Nair, Pradeep M. K. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Hormonal imbalances are common among the women who are in the halfway of their reproductive age. There are lot of factors like stress, diet, lifestyle etc. which contributes to this hormonal dysfunctions. However these factors are merely addressed by the existing management strategies. A 37 year old female presented with hypothyroidism and associated hyperprolactinemia had undergone Naturopathy and yoga interventions for a period of 18 months. Her baseline TSH and prolactin levels were 9.2 U/ml and 34 ng/ml respectively. Her anti-mullerian hormone (AMH) levels also fell down to 0.3 ng/ml. Naturopathy and yoga based lifestyle interventions including hydrotherapy, mud therapy, yoga therapy and acupuncture were given for different durations has streamlined the hormone levels to normal range (TSH-4.6 U/ml, prolactin- 19.6 ng/ml, AMH-2.6 ng/ml). The results indicate that naturopathy and yoga has a positive role in reinstating the hormonal homeostasis. However large scale studies are warranted to bestow better care.